Social media engagement and customer experience: A comparative study of hotels and restaurants in Calabar Metropolis (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
In today's digital age, social media engagement has become a crucial component of customer experience in the hospitality industry. This study compared the social media engagement practices of hotels and restaurants in Calabar Metropolis and their impact on customer experience and patronage. Utilizing a cross-sectional approach, the research design incorporated both quantitative and qualitative data collection techniques. Quantitative data were gathered through structured questionnaire distributed to customers and hospitality busin esses, while qualitative data were obtained from in-depth interviews with social media managers and customer service representatives. The study sampled 15 hotels and 15 restaurants, analyzing their social media activities on platforms such as Facebook, Instagram, and Twitter over a six-month period. Key metrics assessed included response time, content quality, interaction frequency, and customer feedback. Additionally, customer experience was measured through surveys focusing on satisfaction, loyalty, and overall perception of the businesses’ social media presence. Findings revealed significant differences in social media engagement between hotels and restaurants. Hotels tended to have more structured and professional social media strategies, leading to higher levels of customer satisfaction and loyalty. In contrast, restaurants often engaged in more frequent but less formal interactions, which, while fostering a sense of community, sometimes resulted in inconsistent customer experiences. Both sectors benefited from prompt responses and high-quality content, but the impact was morepronounced in the hotel industry due to the typically longer customer decision -making process for accommodations. This study concludes that effective social media engagement is critical for enhancing customer experience and patronage in the hospitality sector. Recommendations include adopting a balanced approach to social media interactions, investing in training for social media managers, and leveraging customer feedback to continuously improve service quality. Future research should explore the long-term impacts of social mediastrategies on business performance and customer loyalty in hotels and restaurants in Calabar.
Keywords: Social Media; Engagement; Customer Experience; Hospitality Industry; Calabar Metropolis